Using Student Actors and Video-Mediated Reflection to Promote Preservice Teachers’ Ability to Enact Responsive Teaching - Chan, Kennedy; Kit, Steven Ka; Ho, Roy Ka (Innovations in Science Teacher Education, 2020)
This paper describes a teaching intervention that promotes secondary preservice science teachers’ (PSTs’) ability to enact responsive teaching. The intervention uses a modified version of rehearsals (Lampert et al., 2013) to enhance PSTs’ ability to enact a core practice: eliciting, interpreting, and using student thinking. In the intervention, PSTs have opportunities to decompose the core practice represented in classroom video clips and to approximate the practice in rehearsals. The intervention has three unique features: (1) student actors who simulate the complex classroom interactions inherent in responsive classrooms; (2) opportunities to view and analyze how different teachers (i.e., own, peers, and unfamiliar teachers) enact the core practice; and (3) opportunities for PSTs to reflect upon their own rehearsal videos filmed from multiple vantage points in the same classroom using innovative video technology such as point-of-view (POV) camera goggles. We describe what we have learnt from analyzing the PSTs’ views on the intervention in terms of their perceived learning from the intervention as well as whether and how the unique features of the intervention supported their learning. We also share the lessons learned and advice that we would like to share with other science teacher educators, especially in terms of how to better use and integrate innovative video technology such as POV footage into the teaching interventions to promote responsive teaching.